2023
DOI: 10.3390/ijms241612550
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Young Serum Contribute to the Restoration of Age-Related Brain Transcriptomes and Cognition in Old Mice

Abstract: We have previously demonstrated that circulating extracellular vesicles (EVs) are essential to the beneficial effect of young serum on the skeletal muscle regenerative cascade. Here, we show that infusions of young serum significantly improve age-associated memory deficits, and that these effects are abolished after serum depletion of EVs. RNA-seq analysis of the choroid plexus demonstrates EV-mediated effects on genes involved in barrier function and trans-barrier transport. Comparing the differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…We computed age-correlations of z-score normalized gene counts for all human brain regions in the GTEx dataset 33 , the Tabula Muris Senis (TMS) dataset 5 , and an additional mouse Hypothalamus aging cohort (GSE157025). Similarly, we calculated the enriched pathways for several "anti-aging" treatments like young serum injections 34 , the platelet factor PF4 35 , sport in humans 36 , and krilloil in C. elegans 37 . An unbiased clustering analysis revealed that the aging-trajectories of C. elegans, mouse, and humans cluster together.…”
Section: Comparison With Mammalian Brain Agingmentioning
confidence: 99%
“…We computed age-correlations of z-score normalized gene counts for all human brain regions in the GTEx dataset 33 , the Tabula Muris Senis (TMS) dataset 5 , and an additional mouse Hypothalamus aging cohort (GSE157025). Similarly, we calculated the enriched pathways for several "anti-aging" treatments like young serum injections 34 , the platelet factor PF4 35 , sport in humans 36 , and krilloil in C. elegans 37 . An unbiased clustering analysis revealed that the aging-trajectories of C. elegans, mouse, and humans cluster together.…”
Section: Comparison With Mammalian Brain Agingmentioning
confidence: 99%
“…EVs encapsulate a diverse array of biomolecules, reflecting the composition and physiological state of their parent cells. Proteomic, lipidomic, and nucleic acid analyses have revealed that EV cargo encompasses proteins involved in cell signaling, membrane trafficking, and cytoskeletal organization, as well as nucleic acids such as microRNAs, mRNAs, and DNA fragments [28][29][30][31][32]. Importantly, the selective packaging of cargo into EVs is governed by specific sorting mechanisms, including protein post-translational modifications, RNA-binding proteins, and lipid raft domains [33].…”
Section: Evs As Key Mediators Of Intercellular Communicationmentioning
confidence: 99%